Sistem Pendukung Keputusan Terhadap Laptop Yang Diminati Konsumen Menggunakan Metode SAW, WP Dan TOPSIS - Nina Amelia Silitonga; Tabah Adi Wiguna; Luthfi Hanan Dio Samartha; Muhammad Baidawi (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
The rapid development of technology, especially in the digital realm, greatly affects the development of current laptop features and specifications. With the development of increasingly diverse features and specifications, it often makes users confused in choosing a laptop that suits the needs of users. The type of data that the author uses is primary data obtained through interviews and direct observation of laptop users. The purpose of this study is to help laptop users in choosing a laptop that suits their needs. In this study, the author aims to design and build a selection decision support system on a laptop, the methods that the author uses are the Simple Additive Weighting (SAW), Weighted Product (WP) and Topsis methods. The use of a Decision Support System (SPK) is expected to help potential consumers to more easily consider choosing a laptop that suits their wishes.